Qualidade de muda e desenvolvimento final a campo de abobrinha e beterraba a partir de diferentes substratos e bandejas - Farinacio, Dione (2011)
The Southwest Parana region is characterized by presenting the significant participation of family farmers. In this context, horticulture has emerged as an important alternative source of income for these farmers, and thus is of importance to the region. However, for this activity to evelop their full potential, we must develop technologies suited to local conditions, particularly to reduce dependence on external inputs and to reduce production costs. In this sense, it was proposed this study in order to evaluate the production of seedlings of zucchini and beet on trays and the production of crops with these seedlings implanted as an alternative to direct sowing in their own beds usually employed in the region. The experiment was carried at UTFPR – campus Pato Branco, with the use of different substrates formulated on the waste coal, humus and vermiculite mixed in different proportions, and as shown by the commercial substrate Húmus Fertil®, packed in trays of 128 and 200 cells. The study involved the performance of four experiments, and at first we evaluated the quality of seedlings of zucchini grown with these substrates and pans, in the second evaluated the production of beet seedlings including direct seeding as a witness, in the third, evaluated the production of squash seedlings from the first experiment, and in the fourth experiment, we evaluated the production of sugar beet. In experiments 01 and 03 were initially evaluated the percentage of emergence speed rate of emergence. Then at 30 days after sowing, the seedlings were evaluated for the variables plant height, stem diameter, leaf number, leaf area, fresh and dry biomass of shoots and roots. For the trials 02 and 04, the transplant was done 30 days after sowing. In experiment 02, the fruits of zucchini were harvested when they reached the point of sale (length 15-20 cm), harvesting them every two days until finalize the production. We evaluated the variables: the diameter of the fruit, fruit number and total yield (in Mg ha-1). In experiment 04, were examined 55 days after transplanting, determining plant height, leaf number, leaf area and dry weight of shoots, the diameter and the weight of tuberous roots. The results showed that the chemical characteristics of substrates significantly influenced the quality of plants, especially the pH and the calcium/magnesium in the case of zucchini, and the ratio of manganese and phosphorus/zinc, in the case of beet. It was noted also that the volume of substrate used in the nursery significantly affect the quality of plants, and the 128 trays (larger volume) produced seedlings of better quality than the tray 2001 cells. The quality of the switches used significantly affected the yield and in the case of zucchini yield was observed between 7,9 and 24,1 Mg ha-1 and in the case of beet, between 22,3 and 59,0 Mg ha-1.